Ecology and conservation of the jacutinga Pipile jacutinga in the Atlantic Forest of Brazil - Galetti, Mauro [UNESP]; Martuscelli, Paulo; Olmos, Fábio; Aleixo, Alexandre (Elsevier, 1997)
The jacutinga Pipile jacutinga was formerly one of the most abundant game bird cracids in the Atlantic forest of Brazil. Nowadays this species is vulnerable to extinction due to hunting and habitat loss. The ecology of the jacutinga was studied at Parque Estadual Intervales, Sao Paulo, Brazil from October 1993 to December 1995 and in adjacent areas. Jacutingas were observed to feed mainly on the sugar-rich fruit of 41 species. We recorded a low index of abundance for the jacutinga (0.018) or c.1.7 birds/km2 at Intervales, one of the best protected areas within their range. Surveys carried out in the Atlantic forest of Sao Paulo found jacutinga populations in 14 localities. Probably < 1500 birds survive in the best protected areas. The species' stronghold in southeastern Brazil is in the mountains of Serra de Paranapiacaba, an area protected by several parks suffering from hunting and palm heart harvesting and threatened by a hydroelectric project.
Keywords: Atlantic forest; Brazil; Conservation; Cracidae; Diet; Frugivory; conservation status; endangered bird; jacutinga; protected area; Brazil, Parana State, Serra de Paranapiacaba; Brazil, Sao Paulo State, Parque Estadual Intervales; Brazil, Sao Paulo State, Serra de Paranapiacaba; Aves; Paranapiacaba; Pipile jacutinga